2009
DOI: 10.1063/1.3276292
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence structure of open channel flows over permeable and impermeable beds: A comparative study

Abstract: The behavior of turbulent open channel flows over permeable surfaces is not well understood. In particular, it is not clear how the surface and the subsurface flow within the permeable bed interact and influence each other. In order to clarify this issue we carried out two sets of experiments, one involving velocity measurements in open channel flows over an impermeable bed composed of a single layer of spheres, and another one where velocities were measured over and within a permeable bed made of five such la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
146
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(171 citation statements)
references
References 31 publications
21
146
2
Order By: Relevance
“…This makes C. Manes, D. Poggi and L. Ridolfi the results of the present study directly comparable with the literature pertaining to aquatic and atmospheric canopy flows (Ghisalberti & Nepf 2002;Poggi et al 2004;Finnigan et al 2009), and also with the DNS of Breugem et al (2006), but to a lesser extent with flows over permeable granular walls (Manes et al 2009;Sarkar & Dey 2010;Detert, Nikora & Jirka 2010). The reason is that the latter class of porous media is characterized by large roughness elements, which makes the effects of roughness and permeability both significant.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This makes C. Manes, D. Poggi and L. Ridolfi the results of the present study directly comparable with the literature pertaining to aquatic and atmospheric canopy flows (Ghisalberti & Nepf 2002;Poggi et al 2004;Finnigan et al 2009), and also with the DNS of Breugem et al (2006), but to a lesser extent with flows over permeable granular walls (Manes et al 2009;Sarkar & Dey 2010;Detert, Nikora & Jirka 2010). The reason is that the latter class of porous media is characterized by large roughness elements, which makes the effects of roughness and permeability both significant.…”
Section: Discussionsupporting
confidence: 79%
“…In the literature, this problem has been overcome by following two approaches. The first, particularly used in the study of flows over granular beds, involves a comparative analysis between flow statistics measured over rough impermeable and rough permeable walls characterized by the same surface roughness texture (Zagni & Smith 1976;Manes et al 2009). For example Manes et al (2009) present a comparison between statistics of velocities measured in open channel flows over an impermeable wall made of one layer of beads and a permeable wall made of five of such layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulent eddies in the water column of a stream, for example, can cause flow across the sediment-water interface in the presence or absence of bed forms. 33 Third, plants and animals colonizing the hyporheic zone can exert profound impacts on stream-sediment exchange, by forming mounds across which pumping occurs, inducing pore water flow within sediments, and structuring the permeability field with burrows and roots (reviewed in 34 ). Fourth, at a larger scale geomorphic features of a stream such as riffle-pool sequences, debris dams, meander bends, and regional groundwater flow all influence hyporheic exchange.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nikora (2009) extended the use of the double-averaging methodology to develop a theoretical expression that explicitly showed that the friction factor can be accounted for by six additive components, of which only three are present in two-dimensional uniform spatially-averaged flow without secondary currents: viscous stress, turbulent stress and forminduced stress. The contribution of the form-induced stress, ũw , has recently attracted substantial attention as it has been shown to play an important role in the overall streamwise momentum balance in the near-bed region (Aberle, Koll, & Dittrich, 2008;Dey & Das, 2012;Ferreira et al, 2010;GimenezCurto and Corniero, 1996;Gimenez-Curto and Corniero Lera, 2003;Manes, Pokrajac, Coceal, & McEwan, 2008;Manes, Pokrajac, & McEwan, 2007;Manes, Pokrajac, McEwan, & Nikora, 2009;Mignot, Barthelemy, & Hurther, 2009a,b;Nikora et al, 2007b;Sarkar & Dey, 2010). Indeed, Gimenez-Curto and Corniero (1996) and Gimenez-Curto and Corniero Lera (2003) suggested that at very low submergences the form-induced stress could become the dominant component in the streamwise momentum balance.…”
Section: Introductionmentioning
confidence: 99%